The Crime of Genocide and its Implications in Law Number 39 of 1999 Concerning Human Rights - Daeng M, Mohd. Yusuf; Saputra, Dodi Ripo; Dony, Mulian; Siregar, Hanipah; Imelda, Rezki (Journal of Law and Humanity Studies, 2024)
Genocide crimes are often associated with crimes against humanity, but when examined more closely, genocide crimes differ from crimes against humanity. Genocide crimes target groups such as nations, races, ethnicities, or religions, whereas crimes against humanity are directed at citizens and civilians. Additionally, genocide crimes can annihilate part or all of a group, whereas crimes against humanity do not have such specifications or conditions. The demands for resolving human rights violation cases led to the creation of Law Number 39 of 1999 concerning Human Rights, followed by Law Number 26 of 2000 concerning Human Rights Courts, which aims to address various human rights violation issues, particularly serious human rights violations. Article 7 of the Human Rights Court Law states that genocide crimes are severe human rights violations due to actions such as killing, causing severe suffering, extermination, coercion by groups, and forcibly transferring children from one group to another. Thus, this human rights court law explicitly threatens the perpetrators. The method used is normative legal research. Based on the research results, it is known that Genocide Crimes and Their Implications in Law Number 39 of 1999 concerning Human Rights show that genocide is one of the most serious forms of human rights violations, involving systematic efforts to destroy certain groups based on ethnicity, religion, or race. Law Number 39 of 1999 concerning Human Rights does not specifically and in detail regulate genocide crimes and their elements. This results in a lack of a strong and comprehensive legal framework to prosecute genocide perpetrators and provide justice and legal certainty for victims. Law Number 26 of 2000 concerning Human Rights Courts in Indonesia is considered inadequate to handle serious human rights violations. Several weaknesses identified include procedural law still referring to the Criminal Procedure Code (KUHAP), which complicates the proof process, and ambiguities in applying regulations due to the incomplete "elements of crimes" stipulated. This results in a lack of effectiveness in prosecuting serious crimes like genocide, which are often triggered by ethnic, religious, and racial factors. The prohibition of genocide crimes is regulated through international and national laws. However, resolving serious human rights violations within the Indonesian criminal justice system based on Law Number 26 of 2000 has not succeeded in creating legal certainty and justice for the victims of violations in East Timor